Image processing of computerised visual field data. Issue 3 (March 1995) - Fitzke, F W; Crabb, D P; McNaught, A I; Edgar, D F; Hitchings, R A
Abstract : BACKGROUND--Computerised perimetry is of fundamental importance in assessing visual function. However, visual fields are subject to patient response variability which limits the detection of true visual loss. METHODS--A method of improving the repeatability of visual field data was demonstrated by applying techniques used in image processing. An illustrative sample of nine normals and nine patients with field loss was used. Two successive Humphrey fields were selected for each subject. Repeatability was defined as the standard deviation of the pointwise differences between sensitivity values of the reference field and repeat field. The field data were then separately subjected to Gaussian and median image processing filters and the repeatability was compared with the unprocessed field results. RESULTS--Improvement in repeatability, by a factor of approximately 2, was demonstrated by both processes. CONCLUSION--These techniques may improve the reliable detection of loss of visual function using computerised perimetry.